Gas geochemistry of the hot springs gas in Fujian province, SE China: insight into the deep faults and seismic activity - Liao, Lixia; Zhou, Yueyong; Lin, Zhiying; Wang, Xiaowei; Chen, Wei; Li, Jiyu; Zheng, Chenhe; Yu, Wenjun; Li, Xingmei; Liu, Jianda (Frontiers in Earth Science, 2023)
Fujian province is located at the forefront of the South China continental margin, situated on the edge of the Circum-Pacific seismic belt, and it is one of the regions with the most active neotectonic and geothermal activities in Chinese mainland. To explore the geochemical signals of hot spring gases to tectonic activity and earthquakes, a collection of geothermal gas samples was collected from 29 locations in Fujian from January 2021 to December 2022 (many of which were multiply collected at several sites quarterly). The gas samples were tested for their gas composition, helium, neon, carbon isotopes, radon contents, and gas flow rates. The results show that the dominant component of the hot spring outgassing is N2, and the increase in CO2 content is often associated with the increasing 13C. The variation range of the helium isotope ratio (3He/4He) in the hot spring gases is between 0.06 and 2.20Ra, and Rc/Ra varies between 0.06 and 1.58, with peak values occurring at the intersections of deep faults. Radon contents range from 18 to 2000 Bq/L. Calculations revealed that the maximum proportion of mantle-derived helium is 30.2%, and the mantle-derived heat contribution ranges from 37.6% to 63.4%. These data indicate a significant mantle degassing process in Fujian, with a high degree of mantle-crust connectivity, and mantle-derived heat as the main source of geothermal activity in the area. Comparative analysis with regional seismic activity indicates that areas with relatively strong upwelling of deep fluids are the main regions of regional seismic activity, and seismic intensity is positively correlated with mantle-derived heat flow. Thus, deep thermal fluid actives are closely genetically correlated to regional seismic activity. Additionally, the correlation analysis with the Taiwan ML6.0 earthquake suggests that high 3He/4He, δ13CCO2 values of hot spring gas and gas flow velocity in Nancheng Hot Spring (QZ6) indicate significant short-term and imminent anomaly indications preceding ML6.0 earthquakes in the Taiwan region.